ESENSI WARIGA DALAM TUTUR MEDANG KEMULAN - I Made Gami Sandi Untara; Ida Bagus Wika Krishna (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2023)
Medang Kemulan's text is one of the many text containing the teachings of Shiva. Judging from the language used and the sloka texts contained in it, it appears that the Medang Kemulan lontar is an old lontar. Tutur Medang Kemulan not only teaches about the teachings of wariga (kala or time) but also emphasizes the teachings of philosophy (Tattwa), namely ethics and human philosophy applied in community life. Tutur Medang Kemulan also teaches about regulating social institutions, especially Balinese society, which is widely discussed. Apart from being an understanding of the prohibition of incestuous marriage, Tutur Medang Kemulan also contains Hindu religious teachings, the aim of which is to realize human social life with individuals who are virtuous in accordance with the teachings of religious literature. Apart from that, in Tutur Medang Kemulan the teachings of self-control regarding human life are taught, namely a person's ability not to do things that are not good or appropriate. In general, this research aims to find out and understand the essence of the wariga teachings contained in Tutur Medang Kemulan so that it can be used as a guide by Hindus and the wider community regarding determining good and bad days. This type of research is qualitative research. The data source used is primary data sourced from literature/libraries. Data collection techniques were carried out using library methods. This research uses data analysis methods with qualitative descriptive techniques.Keywords: Medang Kemulan, Wariga